THE INFLUENCE OF INDIVIDUAL CHARACTERISTICS, JOB CHARACTERISTICS AND ORGANIZATIONAL SUPPORT TO THE ORGANIZATION’S COMMITMENT MEDIATED PERSON ORGANIZATION FIT (A CASE STUDY ON THE PRODUCTION EMPLOYEES OF PT. LINTANG KEJORA SEMARANG) - Patricia Dhiana Paramita (Universitas Pandanaran, 2015)
PT. Lintang Kejora Semarang where the person experiencing problems in thecompany's organization fit so low that adversely affects the employee organizationalcommitment. Presumably it is motivated by a lack of individual characteristics, jobcharacteristics and organizational support. Formulation of the problem in this research ishow the efforts of the management of PT. Lintang Kejora Semarang improve organization fitperson with a positive impact for the commitment of the organization.The population in this study were all employees working in the production amounted to100 people. The sampling technique using census method. Data analysis using multipleregression linear 2 stages and goodness of fit. Based on the analysis, it is known thatindividual characteristics, job characteristics and organizational support positive andsignificant impact on the organization fit person either partially or simultaneously. Personorganization fit positive and significant impact on organizational commitment.Keywords : individual characteristics, job characteristics, organizational support, personorganization fit and organizational commitment